Practicality of Acute and Transitional Care and its consequences in the era of SwissDRG: a focus group study - Tenzin Wangmo; Yvonne Padrutt; Insa Koné; Thomas Gächter; Bernice S. Elger; Agnes Leu (BMC, 2019)
Abstract Background Switzerland recently introduced Acute and Transitional Care (ATC) as a new financing option and a preventive measure to mitigate potential side effects of Swiss Diagnosis Related Group (SwissDRG). The goal of ATC was to support patients who after acute treatment at a hospital require temporary increased professional care. However, evidence is lacking as to the practicality of ATC. Methods Using qualitative focus group methodology, we sought to understand the implementation and use of ATC. A purposive sample of forty-two professionals from five Swiss cantons participated in this study. We used a descriptive thematic approach to analyse the data. Results Our findings first reveal that ATC's implementation differs in the five cantons (i.e. federal states). In two cantons, only ambulatory variant of ATC is used; in one canton only stationary ATC has been created, and two cantons had both ambulatory and stationary ATC but preferred the latter. Second, there are intrinsic practical challenges associated with ATC, which include physicians' lack of familiarity with ATC and its regulatory limitations. Finally, participants felt that due to shorter hospital stays because of SwissDRG, premature discharge of patients with complex care needs to stationary ATC takes place. This development does not fit the nursing home concept of care tailored to long-term patients. Conclusion This empirical study underscores that there is a strong need to improve ATC so that it is uniformly implemented throughout the country and its application is streamlined. In light of the newness of ATC as well as SwissDRG, their impact on the quality of care received by patients is yet to be fully understood. Empirical evidence is necessary to improve these two measures.